Exoskeleton-assisted training to enhance lower limb motor recovery in subacute stroke: does timing matter? A pilot randomized trial - Schröder, Jonas; Yperzeele, Laetitia; Embrechts, Elissa; Loureiro-Chaves, Renata; Hallemans, Ann; Lafosse, Christophe; Truijen, Steven; Kwakkel, Gert; Saeys, Wim (Frontiers in Stroke, 2024)
Background Lower limb motor recovery, including abnormal muscle synergies, occurs mainly within the first 5–8 weeks after a stroke. This suggests the importance of delivering impairment-focused therapies, such as therapeutic robots that promote symmetric gait, during this time-sensitive period, following the principle of “the earlier, the better.” Objective First, to compare early robotic training (ERT) with usual care (UC) against UC alone on restoring intralimb muscle synergies and interlimb symmetry during functional tasks; Second, to investigate whether ERT is superior to delayed robotic training (DRT) starting after the proposed time-sensitive period. Methods This observer-blinded, randomized pilot trial with crossover design involved 19 nonambulatory adults included within 14 days poststroke. Those allocated to ERT (N = 10) received immediately 4 weeks of training (16 sessions, 4× /week) with the Ekso GT® above UC and were compared with the DRT group (N = 9) who received UC alone at this point. Thereafter a 3-week UC period followed to investigate sustainability of ERT and the interventional roles were exchanged; at about week 8 poststroke DRT subjects started the same experimental robotic protocol and ERT subjects continued UC as controls. Outcomes included changes in Fugl-Meyer lower extremity scores (FM-LE) reflecting muscle synergies, weight-bearing asymmetry (WBA), and dynamic control asymmetry (DCA) during quiet standing. Functional ambulation category (FAC) was used to classify walking independence (cut-off ≥4). Results A trend toward earlier reacquisition of walking independence favoring ERT with UC over UC was not accompanied by differences in FM-LE, WBA, or DCA (first objective). Thereafter, DRT with UC did not yield any significant changes relative to UC, such that no between-group differences were found favoring restorative effects of ERT over DRT (second objective). Conclusion This pilot trial shows the feasibility of investigating a wearable exoskeleton as an adjunct therapy in subacute stroke. Nevertheless, our preliminary findings suggest that motor recovery of lower limb muscle synergies was not enhanced by 4 weeks of robotic training to reduce compensations with the less-affected side, irrespective of the timing of application. Trial registration ClinicalTrials.gov, identifier: NCT03727919.